1996
DOI: 10.1001/archinte.1996.00440050111012
|View full text |Cite
|
Sign up to set email alerts
|

Change in Depression as a Precursor of Cardiovascular Events

Abstract: Among elderly persons, a significant and substantial excess risk of death and stroke or myocardial infarction was associated with an increase in depressive symptoms over time, which may be a marker for subsequent major disease events and warrants the attention of physicians to such mood changes. However, further studies of casual pathways are needed before wide-spread screening for depression in clinical practice is to be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(86 citation statements)
references
References 36 publications
4
79
0
3
Order By: Relevance
“…Also, depressive symptoms that are not sufficient in magnitude to meet the criteria for major depression occur at least as commonly among cardiac patients. 2,3 Recent epidemiological studies evaluating the relationship between depression and CAD among healthy [3][4][5][6][7][8][9][10][11] and CAD [12][13][14][15][16][17][18][19] populations consistently demonstrate a significant prospective relationship between the occurrence of major depression episodes and the incidence of cardiac events (Table 1). Two additional findings are notable.…”
Section: Depression and Related Syndromesmentioning
confidence: 99%
“…Also, depressive symptoms that are not sufficient in magnitude to meet the criteria for major depression occur at least as commonly among cardiac patients. 2,3 Recent epidemiological studies evaluating the relationship between depression and CAD among healthy [3][4][5][6][7][8][9][10][11] and CAD [12][13][14][15][16][17][18][19] populations consistently demonstrate a significant prospective relationship between the occurrence of major depression episodes and the incidence of cardiac events (Table 1). Two additional findings are notable.…”
Section: Depression and Related Syndromesmentioning
confidence: 99%
“…In the present study, a subsyndromal depressive mood was assessed by the DEEX scale, which is among the less rigorous options to assess depressive mood although a recent reexamination of its validity and reliability is promising. 15 Clinically, the DEEX scale identified symptoms of reduced vitality, weakness and 'vital exhaustion' 44 but without a negative self-concept and feelings of guilt feelings, 45 which provides sufficient coverage for all important facets of subsyndromal depressive mood of negative affectivity in the context of cardiovascular medicine. 46,47 Additionally, depression was measured at one time point, so that transient states of depression could not be distinguished from persistent states.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 99%
“…In the last fifteen years this link has become the focus of a growing literature of prospective, epidemiological studies (Carney et al, 1988;Thomas et al, 1992;Andaetai, 1993;Aromaa et al, 1994;Vogt et al, 1994;Frasure-Smith et al, 1995;Lapaneefa/., 1995;Wassertheil-Smollerefa/., 1996;Barefoot & Schroll, 1996;Pratt et al, 1996;Bingefors et al, 1996;Ford et al, 1998;Sesso et al, 1998;Cohen et al, 2000;Penninx et al, 2001). Almost all have reported some positive, statistically significant association of depression with cardiovascular disease (CVD), although one found the association with change in depression status rather than baseline depression (Wassertheil-Smoller et al, 1996), and another found the association with all-cause mortality but not CVD mortality (Vogt et al, 1994). One did not report any association at all (Thomas et al, 1992).…”
Section: Hillel W Cohen and James Davidmentioning
confidence: 99%